2015
DOI: 10.2967/jnumed.115.154575
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Traumatic Brain Injury by Increased 64Cu Uptake on 64CuCl2 PET/CT

Abstract: Copper is a nutritional trace element required for cell proliferation and wound repair. Methods To explore increased copper uptake as a biomarker for noninvasive assessment of traumatic brain injury (TBI), experimental TBI in C57BL/6 mice was induced by controlled cortical impact, and 64Cu uptake in the injured cortex was assessed with 64CuCl2 PET/CT. Results At 24 h after intravenous injection of the tracer, uptake was significantly higher in the injured cortex of TBI mice (1.15 ± 0.53 percentage injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Our findings are in line with previous studies that applied [ 64 Cu]CuCl 2 as a tracer for investigation of cerebral copper metabolism in aging mice with autoradiography [25], study of changes of cerebral copper metabolism in a mouse model of Menkes disease [26], as well as diagnostic imaging of traumatic brain injury [13]. To determine whether 64 Cu radioactivity measured by PET/CT is correlated with the concentration of endogenous copper ions in mouse tissues, copper concentration of mouse tissues was determined by ICP-MS and correlated with 64 Cu biodistribution in Balb/c mice on [ 64 Cu]CuCl 2 -PET/CT imaging (Fig 3).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are in line with previous studies that applied [ 64 Cu]CuCl 2 as a tracer for investigation of cerebral copper metabolism in aging mice with autoradiography [25], study of changes of cerebral copper metabolism in a mouse model of Menkes disease [26], as well as diagnostic imaging of traumatic brain injury [13]. To determine whether 64 Cu radioactivity measured by PET/CT is correlated with the concentration of endogenous copper ions in mouse tissues, copper concentration of mouse tissues was determined by ICP-MS and correlated with 64 Cu biodistribution in Balb/c mice on [ 64 Cu]CuCl 2 -PET/CT imaging (Fig 3).…”
Section: Discussionsupporting
confidence: 91%
“…[ 64 Cu]CuCl 2 -PET/CT imaging of Balb/c mice was performed using a method described previously [79, 13]. Briefly, Balb/c mice were anesthetized by 3% isoflurane in 100% oxygen (3 L/min) at room temperature, using an isoflurane vaporizer (Summit Anesthesia Solutions, Salt Lake City, UT).…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis [ 144 ] and the following investigations [ 105 , 145 ] revealed a lower total Cu in AD, while the level of labile Cu is higher in most of the brain areas affected by this disease [ 105 ]. Alzheimer’s brain tissues and the cortexes of transgenic animals with severe brain damage showed the high Cu 2+ ions-binding capacity [ 105 , 146 ]. Additionally, the APPsw/0 mouse model study reported parenchymal Aβ plaques, but no damage to neurons has been observed ( Table 1 ) [ 147 , 148 ].…”
Section: Copper Ion Implication In Admentioning
confidence: 99%
“…Copper is required for brain development and physiology although the role of copper in brain aging remains to be elucidated. Radionuclide 64 Cu is a positron emitting copper isotope and 64 CuCl 2 was used as a radiotracer for noninvasive assessment of disturbance of cerebral copper fluxes in traumatic brain injury [ 28 ] and age-dependent changes of copper fluxes in Atp7b -/- knockout mouse model of Wilson’s disease [ 25 ]. Applying 64 CuCl 2 -PET/CT imaging in a mouse model of brain aging, we present data that show age-related differences in brain copper fluxes across the life span.…”
Section: Discussionmentioning
confidence: 99%